Influenza Virus and its Relationship with Bacterial Otitis Media: A Review - H. Al-Wazni, Zahra; Ateyah A. Al-Nasrawi, Adil (Kerbala Journal of Nursing and Health Sciences., 2025)
Influenza virus is a common viral pathogen that can contribute to the progress of otitis media, particularly in children. The connection between influenza and otitis media primarily involves the virus’s impact on the upper respiratory tract. Influenza infection can lead to inflammation and problems with the Eustachian tube, which disrupts normal the middle ear ventilation along with promotes fluid accumulation. This environment facilitates secondary bacterial infections or may allow direct viral invasion of the middle ear. Moreover, influenza weakens local immune defences, increasing susceptibility to ear infections. Clinical observations often show that otitis media occurs a few days following the start of flu signs such as fever, nasal congestion, and cough. Preventive measures, such as annual influenza vaccination, have been shown to reduce the incidence of otitis media through reducing its incidence and severity of influenza infections. Early diagnosis and appropriate treatment, based on if the etiologic is bacterial or viral, are essential for managing complications. The different kinds of ear infections and the associated microorganisms that cause middle ear infections are discussed in this review paper. In order to identify ear infections, we describe the standard methods and clinical trials that employ them.